2021
DOI: 10.3390/ijerph18126292
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Neighborhood Environment Associated with Sarcopenia in Urban-Dwelling Older Adults: The Korean Frailty and Aging Cohort Study (KFACS)

Abstract: Sarcopenia is associated with adverse health outcomes among older individuals. However, little is known about its association with neighborhood environmental factors. We explored the relationship between sarcopenia and perceived neighborhood environmental factors among community-dwelling older adults aged 70–84 years. We analyzed 1778 participants (mean age of 75.9 ± 3.8 years; 54.0% women) who lived in urban areas and underwent dual-energy X-ray absorptiometry from the Korean Frailty and Aging Cohort Study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(64 reference statements)
1
5
0
1
Order By: Relevance
“…The results of multiple logistic regression analysis showed that older adults living in environments with good access to recreational facilities maintained their 5-m walking time performance after one year. Although positive associations between physical function and recreational facilities, which are factors of the physical environment, have been reported in cross-sectional studies [23,26], the present results strengthen the findings because of the longitudinal study design. In addition, good crime safety influenced the maintenance of TUG performance after one year.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of multiple logistic regression analysis showed that older adults living in environments with good access to recreational facilities maintained their 5-m walking time performance after one year. Although positive associations between physical function and recreational facilities, which are factors of the physical environment, have been reported in cross-sectional studies [23,26], the present results strengthen the findings because of the longitudinal study design. In addition, good crime safety influenced the maintenance of TUG performance after one year.…”
Section: Discussionsupporting
confidence: 79%
“…Given the differences in cultural backgrounds between Western and Asian countries, recent studies conducted in Japan [21][22][23], China [24], and South Korea [25][26][27] have provided perspectives from the Asian region. Of these studies, one has examined the relationship between neighborhood physical and social environments and physical function [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenia will have a major impact on the Asian aging population ( 26 ). The diagnosis of sarcopenia is also highly variable due to race, measurement methods, and living environments ( 27 , 28 ). High-altitude hypoxia is considered to be able to facilitate sarcopenia and fat distribution ( 26 , 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%